Sodium bicarbonate (NaHCO3) for controlling powder mildew of ridge gourd, Luffa acutangula (L.) Roxb. - Che Ku Nor Yanti Shaniza C. Ku Mansol.
Powdery mildew is a serious disease on ridge gourd. Systemic chemical fungicides have been effective in controlling this disease. However, they often cause resistant of the pathogen to develop and are very costly. An experiment was conducted in the glasshouse to determine the effectiveness of sodium bicarbonate, NaHC03 against powdery mildew on ridge gourd, Luffa acutangula [L.] Roxb. as an alternative to these systemic fungicides. Disease symptoms initially appeared as white tiny, round, and superficial spots on leaves. Then, the white spots slowly enlarged became powdery and superficial spots and white lesions of fungus later cover all parts of the upper leaves and widespread to the stems. Finally, the infected leaves became chlorosis, brown, shriveled and then leaves dried up and fall. Include here the treatments used in this study, result showed that 2.0% sodium bicarbonate effectively inhibited powdery mildew fungus for in vitro test in which 98.75% of the spores were not germinating while 0.25% 1; of sodium bicarbonate showed the lowest inhibition at 88.37%. For all treatments, the severity of disease increased in time. The effective treatments which show the lowest disease incidence and disease severity was 2.0 % sodium bicarbonate + 1 % white oil. Because there are no significant different between chlorothalonil and 2.0 % sodium bicarbonate + 1 % white oil, they could be used in controlling the powdery mildew with the value of mean disease severity for both were 2.36% and 2.95%. The lower value of AUDPC indicates that the treatment was effective in controlling powdery mildew. The value of chlorothalonil was lowest with 55.9 units2 and the second lowest was 2.0% sodium bicarbonate + 1.0% white oil with the value was 75 unit2. Both of them were not significantly difference because in SAS, they were in the same group. The highest AUDPC was control with 522.9 unit2. For the result of disease progress rate, all the treatments were not significant difference because they were in the same group. The lowest value was chlorothalonil with 0.11 unit/day followed by treatment with 2.0% sodium bicarbonate + 1.0% white oil was 0.12 unit/ day. This study show that 2.0% sodium bicarbonate + 1.0% white oil was as effective as chlorothalonil and therefore can be used as an alternative to chemicals to control powdery mildew.